High and Low Management Input Regimes Result in Similar Net Carbon Sequestration Rates in Zoysiagrass Golf Course Fairway Turf - Ross C. Braun; Dale J. Bremer (Kansas Agricultural Experiment Station Research Reports, 2019)
This study was conducted from 2013–2016 to determine how irrigation and N fertilization may be managed to enhance carbon (C) sequestration in turf. In this study, the annual rate of change in soil organic carbon (ΔSOC) was measured under two management regimes, a high management input regime (HMI) and low management input regime (LMI), in a ‘Meyer’ zoysiagrass (Zoysia japonicaSteud.) golf course fairway. Both management regimes maintained acceptable turf quality and at least 75% green cover during both summers. In both management regimes, soil organic carbon (SOC) increased after the 3.16-yr (1154-d) period indicating that C was sequestered in the soil. The C emissions from turfgrass maintenance practices (mowing, irrigation, and fertilization and pesticide applications) are known as “hidden carbon costs” (HCC). The average gross C sequestration rates for the two treatments were not statistically different at 1046 kg C/ha/yr and 976 kg C/ha/yr in HMI and LMI, respectively, prior to subtracting HCC. Once the total estimated HCC was included, the average net sequestration rate was 412 kg C/ha/yr and 616 kg C/ha/yr in HMI and LMI, respectively, with no statistical differences. Our study indicates high and low management input regimes result in similar net C sequestration rates in zoysiagrass golf course fairway turf.
Keywords: carbon; greenhouse gas; climate change; hidden carbon cost